Students, Approaches and School: School Violence in Colombia, a state of the question - Caballero León, Laura; Garzón Martínez, María Angélica; Martínez Moya, Armando (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: To elaborate an analysis of the study approaches that favored the theoretical construction of school violence in Colombia. Originality/Contribution: To offer an alternative epistemological entry to the studies on school violence in Colombia that considers the interpretation of the students. Method: From a critical perspective, the article presents a historical overview of the emergence of research on school violence in Colombia. Emphasis is placed on the years 2006 to 2016, as this is the period with the highest production of this type of research. Strategies/Information collection: The bibliographic search was carried out digitally with focus on academic and governmental archives, and texts which, in general, had school violence in Colombia as a central theme. This strategy made it possible to establish a relationship between the temporality and the methodological approach of research on Colombian school violence. Conclusions: the study shows that the psychological approach favored studies on school violence in Colombia, with a focus on the treatment and intervention of aggressive behavior of schoolchildren. The understanding of Colombian school violence was defined by experts who talked about coexistence and school members without considering the voice of the students.